OBSERVATION ON THE FEEDING OF NUDIBRANCH Phyllidia varicosa LAMARCK, 1801 ON THE SPONGE Axinyssa cf. aculeata WILSON, 1925 IN CORAL REEFS OF PRAMUKA ISLAND, THOUSAND ISLANDS NATIONAL PARK, INDONESIA - Yasman, Yasman (Makara Journal of Science, 2003)
During three months period observations (November 16 to January 13, 2001) in coral reefs of Pramuka Island Indonesia, the nudibranch Phyllidia varicosa was observed while feeding on the sponge Axinyssa cf. aculeata. During feeding, P. varicosa extended externally the pharyngeal bulb onto the sponge causing visible somatic damage. The behaviors of contracting the body and retracting the rhinopores inside the rhinotube were also observed while feeding. Observations on the feeding of Phyllidia varicosa on the sponge Axinyssa cf. aculeata and the presence of a visible somatic damage on the prey due to predation are reported for the first time.